Integration: the key to implementing the Sustainable Development Goals - Stafford-Smith, Mark; Griggs, David; Gaffney, Owen; Ullah, Farooq; Reyers, Belinda; Kanie, Norichika; Stigson, Bjorn; Shrivastava, Paul; Leach, Melissa; O’Connell, Deborah (Sustainability science, 2017)
On 25 September, 2015, world leaders met at the United Nations in New York, where they adopted the Sustainable Development Goals. These 17 goals and 169 targets set out an agenda for sustainable development for all nations that embraces economic growth, social inclusion, and environmental protection. Now, the agenda moves from agreeing the goals to implementing and ultimately achieving them. Across the goals, 42 targets focus on means of implementation, and the final goal, Goal 17, is entirely devoted to means of implementation. However, these implementation targets are largely silent about interlinkages and interdependencies among goals. This leaves open the possibility of perverse outcomes and unrealised synergies. We demonstrate that there must be greater attention on interlinkages in three areas: across sectors (e.g., finance, agriculture, energy, and transport), across societal actors (local authorities, government agencies, private sector, and civil society), and between and among low, medium and high income countries . Drawing on a global sustainability science and practice perspective, we provide seven recommendations to improve these interlinkages at both global and national levels, in relation to the UN’s categories of means of implementation: finance, technology, capacity building, trade, policy coherence, partnerships, and, finally, data, monitoring and accountability.